2020
DOI: 10.1038/s41398-020-01065-0
|View full text |Cite
|
Sign up to set email alerts
|

Full function of exon junction complex factor, Rbm8a, is critical for interneuron development

Abstract: The formation of the nervous system requires a balance between proliferation, differentiation, and migration of neural progenitors (NPs). Mutations in genes regulating development impede neurogenesis and lead to neuropsychiatric diseases, including autism spectrum disorders (ASDs) and schizophrenia (SZ). Recently, mutations in nonsense-mediated mRNA decay genes have been associated with ASDs, intellectual disability (ID), and SZ. Here, we examine the function of a gene in the exon junction complex, Rbm8a, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 59 publications
2
21
0
Order By: Relevance
“…We next examined the requirement of the presence of each EJC component during neuronal development by conditionally removing each protein from newborn cortical excitatory neurons. For this, we crossed mice carrying floxed alleles for either Eif4a3, Rbm8a or Magoh with Nex -Cre, which drives Cre expression in all newborn glutamatergic neurons of the neocortex around E11.5-12.5 (Goebbels et al, 2006; Mao et al, 2016b; Mao et al, 2015; McMahon et al, 2014; McSweeney et al, 2020). Cre activity was verified by reporter expression of tdTomato in E14.5 Nex -Cre; Eif4a3 lox/+ ; Ai14 lox/+ cortical sections ( Figure S1J ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next examined the requirement of the presence of each EJC component during neuronal development by conditionally removing each protein from newborn cortical excitatory neurons. For this, we crossed mice carrying floxed alleles for either Eif4a3, Rbm8a or Magoh with Nex -Cre, which drives Cre expression in all newborn glutamatergic neurons of the neocortex around E11.5-12.5 (Goebbels et al, 2006; Mao et al, 2016b; Mao et al, 2015; McMahon et al, 2014; McSweeney et al, 2020). Cre activity was verified by reporter expression of tdTomato in E14.5 Nex -Cre; Eif4a3 lox/+ ; Ai14 lox/+ cortical sections ( Figure S1J ).…”
Section: Resultsmentioning
confidence: 99%
“…All animal procedures were approved by the Duke Institutional Animal Care and Use Committee (IACUC) and performed in agreement with the ethical guidelines of the Division of Laboratory Animal Resources (DLAR) from Duke University. We used the following previously described mouse lines: Eif4a3 loxP (Mao et al, 2016b), Rbm8a loxP (McSweeney et al, 2020), Magoh loxP (McMahon et al, 2014) and Neurod6 tm1(cre)Kan ( Nex -Cre) (Goebbels et al, 2006). The following mouse strains were obtained from Jackson Laboratories: C57BL/6J ( wild type ), B6.Cg- Gt(ROSA)26Sor tm14(CAG-tdTomato)Hze /J (Ai14), B6.129S2-Trp53 tm1Tyj /J (p53 LoxP ), and C57BL/6J- Tg(Dcx-DsRED)14Qlu/J ( Dcx ::DsRed).…”
Section: Star Methodsmentioning
confidence: 99%
“…Other brain dysfunctions, including psychosis, agenesis of the corpus callosum and hypoplasia of the cerebellar vermis, are present in TAR patients [ 28 , 29 , 30 ]. Consistent with human patient studies, knockdown and knockout of Rbm8a in a mouse model revealed the critical role of RBM8A in neural progenitor cell (NPC) proliferation, neuronal migration and interneuron development, and loss of function in RBM8A in NPCs causes microcephaly [ 31 , 32 , 33 ]. Moreover, RBM8A plays a key role in adult neurogenesis and in regulating anxiety-related behavior [ 34 ], further supporting the important role of RBM8A in psychiatric diseases.…”
Section: Chromosomal Mapping and Genetic Pathway Of 1q211mentioning
confidence: 80%
“…The role of SMG6 on interneuron progenitors is reminiscent of a recent study showing that exon-junction complex factor RBM8A is critical for interneuron development [ 55 ]. Consistent with the defects of SMG6 deficient interneurons, key transcription factors that control the cell fate of interneuron progenitors were found dysregulated.…”
Section: Discussionmentioning
confidence: 99%